Modified assessment tools for measuring innovativeness level of companies. Issue 1 (1st January 2019) - Purwanggono, Bambang; Amalia, Annindya Nur
Abstract: The innovation role in Indonesia as economic growth and prosperity driver has not been fully optimized. Indonesia ranked 88th from 128 countries that included in the list of world's most innovative countries. It shows that Indonesia must develop and improve itself within several indicators of innovation. One of the assessing aspects is related to the role of industry or company in innovation areas. The companies' role can be assessed more extensively by assessing the innovative excellence of organizations using assessment tools. By identifying the level of innovativeness maintenance and improvement related to better performance are constantly done. Existing assessment tools are modified in order to result in a framework that is easily understandable and suitable with the background of Indonesian companies. Methods used for modifying assessment tools are Delphi method to validate the research sub-variables, Analytical Hierarchy Process (AHP) method to determine the importance weight of each sub-variable, and in-depth interview method to collect the assessment data. The modified assessment tools can be utilized to analyze the strengths and weaknesses of the company evaluated from the innovation excellence aspects so that the company could then determine the maintenance, improvements and the refinements needed. The score of 1, 000 is the maximum value that can be obtained.